2017
DOI: 10.1038/s41467-017-00554-z
|View full text |Cite|
|
Sign up to set email alerts
|

Herbivores rescue diversity in warming tundra by modulating trait-dependent species losses and gains

Abstract: Climate warming is altering the diversity of plant communities but it remains unknown which species will be lost or gained under warming, especially considering interactions with other factors such as herbivory and nutrient availability. Here, we experimentally test effects of warming, mammalian herbivory and fertilization on tundra species richness and investigate how plant functional traits affect losses and gains. We show that herbivory reverses the impact of warming on diversity: in the presence of herbivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
119
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(137 citation statements)
references
References 66 publications
10
119
1
1
Order By: Relevance
“…In this subregion, grazing increased between 1980 and 2010, and studies elsewhere have shown that increased grazing pressure can contribute to preservation of high local-scale species diversity (Chollet, Baltzinger, Le Saout, & Martin, 2014;Kaarlejärvi, Eskelinen, & Olofsson, 2017). Even so, relatively intense grazing pressure can also lead to more homogeneous community composition (Rooney, 2009).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this subregion, grazing increased between 1980 and 2010, and studies elsewhere have shown that increased grazing pressure can contribute to preservation of high local-scale species diversity (Chollet, Baltzinger, Le Saout, & Martin, 2014;Kaarlejärvi, Eskelinen, & Olofsson, 2017). Even so, relatively intense grazing pressure can also lead to more homogeneous community composition (Rooney, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…The decrease of compositional variation in fertile communities in subregion NBs, which is also associated with a change from formerly herb‐rich ( Geranium , Filipendula ) to recent graminoid‐rich ( Elymus , Melica ) composition, may be indicative of grazing‐driven increases of species diversity and compositional homogenization. In this subregion, grazing increased between 1980 and 2010, and studies elsewhere have shown that increased grazing pressure can contribute to preservation of high local‐scale species diversity (Chollet, Baltzinger, Le Saout, & Martin, ; Kaarlejärvi, Eskelinen, & Olofsson, ). Even so, relatively intense grazing pressure can also lead to more homogeneous community composition (Rooney, ).…”
Section: Discussionmentioning
confidence: 92%
“…Studies in the Alps have shown that it is the abandonment of traditional pasture management, rather than increasing temperatures, that is driving the observed tree line ascent there (Braunisch et al., ; Carlson, Renaud, Biron, & Choler, ). Similarly, in the alpine tundra of the Scandes, reindeer and rodent grazing counteract shrub encroachment and tree line ascent (Austrheim & Eriksson, ; Kaarlejarvi, Eskelinen, & Olofsson, ).…”
Section: Discussionmentioning
confidence: 99%
“…, Kaarlejarvi et al. ), and ecosystem responses to altered precipitation regimes may be reversed on the long run due to interactions within and between trophic levels (Suttle et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, under warming, the biological pest control by predators has been shown to be more efficient in organic compared to conventional fields (Murrell and Barton 2017). In turn, plant communities may show opposing responses to warming depending on whether herbivores are present or not (Post and Pedersen 2008, Mooney et al 2009, Kaarlejarvi et al 2017, and ecosystem responses to altered precipitation regimes may be reversed on the long run due to interactions within and between trophic levels (Suttle et al 2007). Therefore, deeper insights into the role of species interactions are fundamental for our understanding of interacting effects of land use and climate change on biodiversity and ecosystems (Urban et al 2016).…”
Section: Introductionmentioning
confidence: 99%